2 Records of the Governor and Company of the Massachusetts Bay 134 (Nathaniel B. Shurtleff ed., 1853) - (:unkn) unknown (My University, 1645)
Required "all inhabitants" to obtain arms for defense of themselves and the country. Muskets are to be full musket boare or basterd musket. No rifles should be under three foot nine inches in length, nor above four foot three inches.
Keywords: REQUIRED POSSESSION